Surviving drought: a framework for understanding animal responses to small rain events in the arid zone. Issue 11 (1st October 2019) - Maute, Kimberly; Hose, Grant C.; Story, Paul; Bull, C. Michael; French, Kristine
Abstract: Large rain events drive dramatic resource pulses and the complex pulse‐reserve dynamics of arid ecosystems change between high‐rain years and drought. However, arid‐zone animal responses to short‐term changes in climate are unknown, particularly smaller rain events that briefly interrupt longer‐term drought. Using arthropods as model animals, we determined the effects of a small rain event on arthropod abundance in western New South Wales, Australia during a longer‐term shift toward drought. Arthropod abundance decreased over 2 yr, but captures of 10 out of 15 ordinal taxa increased dramatically after the small rain event (<40 mm). The magnitude of increases ranged from 10.4 million% (collembolans) to 81% (spiders). After 3 months, most taxa returned to prerain abundance. However, small soil‐dwelling beetles, mites, spiders, and collembolans retained high abundances despite the onset of winter temperatures and lack of subsequent rain. As predicted by pulse‐reserve models, most arid‐zone arthropod populations declined during drought. However, small rain events may play a role in buffering some taxa from declines during longer‐term drought or other xenobiotic influences. We outline the framework for a new model of animal responses to environmental conditions in the arid zone, as some species clearly benefit from rain inputs that do not dramatically influence primary productivity.